2017
DOI: 10.1093/cid/cix753
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Supplementation Increases Spine Bone Mineral Density in Adolescents and Young Adults With Human Immunodeficiency Virus Infection Being Treated With Tenofovir Disoproxil Fumarate: A Randomized, Placebo-Controlled Trial

Abstract: NCT01751646.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…Low dietary vitamin D intake among participants as compared to the Institute of Medicine (IOM) recommended daily allowance (RDA) was ubiquitous across studies. Similarly, dietary calcium intake was well below the RDA in the four studies to report this [ 56 , 57 , 64 , 72 ].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Low dietary vitamin D intake among participants as compared to the Institute of Medicine (IOM) recommended daily allowance (RDA) was ubiquitous across studies. Similarly, dietary calcium intake was well below the RDA in the four studies to report this [ 56 , 57 , 64 , 72 ].…”
Section: Resultsmentioning
confidence: 96%
“…study which used D 2 (ergocalciferol) for supplementation [ 54 ]. Four studies supplemented calcium in conjunction with vitamin D [ 55 , 56 , 57 , 58 ] whereas three studies utilised a multiple-micronutrient supplement which did not contain calcium [ 59 , 60 , 61 ]. There was considerable dosing heterogeneity in regimens, ranging from 200–7,000 IU/day.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the latest version of the European AIDS Clinical Society Guidelines, vitamin D screening in patients receiving ARTs associated with low vitamin D levels is recommended (110). Recent studies in participants receiving EFV or TDF-cART showed that a dosage supplement of 50,000-60,000 IU per month was enough to reach the goal of 25(OH)D ≥30 ng/mL after 6 months (111,112).…”
Section: Antiretroviral Therapymentioning
confidence: 99%